Evaluación del nicho ecológico y estado de conservación del gato colocolo Leopardus colocola (Molina 1782) - Chávez-Villavicencio, César Lautaro (2024)
Until 2021, Leopardus colocola was considered a species distributed across much of South America. However, recent studies have shown that it is a monotypic species, apparently restricted in its distribution to the central-northern region of Chile, distinct from other felines of the same genus. This change in its classification and distribution has sparked debate regarding its conservation status, which now requires a detailed assessment. In this study, we analyzed the species’ geographic distribution using ecological niche modeling and evaluated its conservation status according to the guidelines of the International Union for Conservation of Nature, considering the impact of mining concessions and Chile's road network. Presence records of the species were systematized, and a new ecological niche model was developed. Additionally, the Extent of Occurrence (EOO) and the Area of Occupancy (AOO) were calculated. The fragmentation and projected reduction of the niche model, along with the EOO and AOO, place the species under the Criteria B2ab (i, ii, iii), leading to its classification as “Endangered.” This study provides an updated view of the species' geographic distribution and conservation status in Chile. The results are crucial for future conservation efforts and offer a solid foundation for effective management strategies.